Hand Grip Strength as a Clinical Biomarker for ME/CFS and Disease Severity - Nacul, Luis Carlos; Mudie, Kathleen; Kingdon, Caroline C.; Clark, Taane G.; Lacerda, Eliana Mattos (Frontiers in Neurology, 2018)
Background The diagnosis of myalgic encephalomyelitis (ME/CFS) in research and clinical practice has largely relied on clinical history, which can be subjective in nature. Clinical signs are often subtle, overlap with other conditions, and are not formally included as part of diagnostic workup. The characterisation of clinical signs and biomarkers is needed for better diagnosis and classification of patients and to monitor treatment response. Hand grip strength (HGS) has been used as an objective measure of muscle strength and fatigue, which is a primary symptom of ME/CFS. We assessed the potential usefulness of HGS as a diagnostic marker in ME/CFS. Methods We compared HGS measurements from participants in the UK ME/CFS Biobank, with groups consisting of people with ME/CFS of differing severity (n=272), healthy (n=136), multiple sclerosis (n=76) controls, and others with chronic fatigue not meeting the diagnosis of ME/CFS (n=37). We correlated the maximum and minimum of, and differences between, 3 repeated HGS measurements with parameters of disease severity, including fatigue and pain analog scales, and physical and mental component summaries from the SF-36v2TM questionnaire across recruitment groups. Results HGS indicators were associated with having ME/CFS, with magnitudes of association stronger in severely affected than in mild/moderately affected patients. Compared with healthy controls, being severely affected was associated with a reduction in minimum HGS of 15.3kg (95%CI 19.3-11.3; p<0.001), while being mild/moderately affected was associated with a 10.5kg (95%CI 13.2-7.8; p<0.001) reduction. The association persisted after adjusting for age, sex and body mass index. ME/CFS cases also showed lower values of maximum HGS and significant drops in values from the first to second and third trials, compared to other study groups. There were significant correlations between HGS indicators and clinical parameters of disease severity, including fatigue analog scale (Spearman’s Rho= -0.40, p<0.001), pain analog scale (Rho=-0.38, p<0.001), and physical component summary (Rho=0.42, p<0.001). Discussion HGS is markedly reduced in ME/CFS, particularly in patients with more severe disease, and may indicate muscle and fatigue related symptoms. HGS is a potential diagnostic tool in ME/CFS, and could also be used to enhance patient phenotyping and as an outcome measure following interventions.